2013
DOI: 10.5897/ajpp12.1073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ocimum basilicum on ovary tissue histopathology after exposure to electromagnetic fields (EMF) in rats

Abstract: Plants continue to be a major source of medicines, as they have been throughout human history. Ocillium basilicum has been used since ancient times as a medicine and food and it is known that the antioxidant effect of O. basilicum is beneficial to protect tissue and decreasing carcinogeniceffect of electromagnetic field (EMF), so it was hypothesized that this herb might also provide protection to ovarian tissue against reactive oxygen spaces (ROS). Female wistar rats (n = 40) were allocated to four groups, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…The studies about the effects of EMF on ovarian follicles have shown that oocyte nucleus becomes smaller and changes shape and the number of apoptotic bodies and autophagic vacuoles in granulosa cells increased, compared to the control group ( 26 , 27 ). According to a study conducted by Roshangar et al it was found that exposure to EMF can lead to morphological changes in the oocyte and increasing the nuclear congestion of granulosa cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies about the effects of EMF on ovarian follicles have shown that oocyte nucleus becomes smaller and changes shape and the number of apoptotic bodies and autophagic vacuoles in granulosa cells increased, compared to the control group ( 26 , 27 ). According to a study conducted by Roshangar et al it was found that exposure to EMF can lead to morphological changes in the oocyte and increasing the nuclear congestion of granulosa cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Roshangar et al it was found that exposure to EMF can lead to morphological changes in the oocyte and increasing the nuclear congestion of granulosa cells ( 28 ). EMF exposure in daily life reduces the supply of egg cell in the ovaries and will lead to an increase in infertility ( 7 , 25 , 26 ). It showed that follicle atresia in the ovaries is associated with apoptosis of granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to investigate the effects of electromagnetic field with a frequency of 50 Hz on folliculogenesis and differentiated oocytes of newborn rat pups after pregnancies that were affected by an electromagnetic field. Rats’ ovaries during the post-natal period are rich in quiescent and early-growing oocytes that are surrounded by a layer of granulosa cells (20, 21). Exposure to an EMF during embryonic development can affect folliculogenesis (6) and cause adverse effects on fertility in female mammals (7).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, exposure to extremely low frequency magnetic fields may impair the fertility of female mammals by reducing the ability of follicles to reach the stage of development that is an essential prerequisite for successful reproduction. The EMF exposure in daily life due to reducing supply of oocytes in the ovaries leads to decreasein infertility (7, 21, 24). It has been shown that follicle atresia in the ovaries is associated with apoptosis of granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 An experiment on female rats also proved antioxidant potential of its methanolic extract given at dose of 1.5g/kg in combination with exposure to electromagnetic field (EMF) and results showed significant improvement in various histological parameters of ovaries including granulosa cell apoptosis, fibrosis and venous congestion, when compared with other group that received only EMF exposure. 17 Cyclophosphamide is being frequently used in recent past years to treat malignancies. Major adverse effect of cyclophosphamide, when used in young females having CA breast, is secondary infertility due to its direct effects on primordial and growing follicles resulting in oxidative damage.…”
Section: Introductionmentioning
confidence: 99%